Persistent Endothelial Dysfunction in Coronavirus Disease-2019 Survivors Late After Recovery - Gao, Yi-Ping; Zhou, Wei; Huang, Pei-Na; Liu, Hong-Yun; Bi, Xiao-Jun; Zhu, Ying; Sun, Jie; Tang, Qiao-Ying; Li, Li; Zhang, Jun; Zhu, Wei-Hong; Cheng, Xue-Qing; et al. (Frontiers in Medicine, 2022)
Background Coronavirus disease 2019 (COVID-19) can result in an endothelial dysfunction in acute phase. However, information on the late vascular consequences of COVID-19 is limited. Methods Brachial artery flow-mediated dilation (FMD) examination were performed, and inflammatory biomarkers were assessed in 86 survivors of COVID-19 for 327 days (IQR 318–337 days) after recovery. Comparisons were made with 28 age-matched and sex-matched healthy controls and 30 risk factor-matched patients. Results Brachial artery FMD was significantly lower in the survivors of COVID-19 than in the healthy controls and risk factor-matched controls [median (IQR) 7.7 (5.1–10.7)% for healthy controls, 6.9 (5.5–9.4)% for risk factor-matched controls, and 3.5(2.2–4.6)% for COVID-19, respectively, p < 0.001]. The FMD was lower in 25 patients with elevated tumor necrosis factor (TNF)-α [2.7(1.2–3.9)] than in 61 patients without elevated TNF-α [3.8(2.6–5.3), p = 0.012]. Furthermore, FMD was inversely correlated with serum concentration of TNF-α (r = −0.237, p = 0.007). Conclusion Survivors of COVID-19 have a reduced brachial artery FMD, which is inversely correlated with increased serum concentration of TNF-α. Prospective studies on the association of endothelial dysfunction with long-term cardiovascular outcomes, especially the early onset of atherosclerosis, are warranted in survivors of COVID-19.